The Role of the Church in Public Policy Advocacy - Tuhepary, Yesaya Paskalis Immanuel (Jurnal Indonesia Sosial Sains, 2025)
The growing complexity of social, political, and economic challenges—such as inequality, corruption, environmental degradation, and human rights violations—demands the active involvement of religious institutions in public policy discourse. Historically, churches have played key roles in justice movements, from civil rights to anti-apartheid struggles. In Indonesia, with its diverse religious context, the Church encounters both opportunities and constraints in exercising its prophetic role within governance. This study explores the theological foundations, opportunities, and challenges shaping the Church’s engagement. Using a qualitative-descriptive approach, it synthesizes theological literature, policy analyses, and observations of church involvement in advocacy. Findings indicate that the Church’s potential for influence rests on four pillars: (1) moral authority grounded in biblical mandates for justice (Micah 6:8; Isaiah 1:17); (2) wide social networks enabling community mobilization; (3) the capacity for prophetic critique of unjust structures; and (4) partnerships with civil society and government institutions. Yet, advocacy effectiveness is constrained by political instrumentalization risks, the challenge of operating within religious pluralism, and the difficulty of translating moral rhetoric into transformative action. The study concludes that the Church’s theological commitment to justice, compassion, and human dignity, together with its organizational capacity, positions it as a vital moral force for promoting equitable public policies. Strengthening theological education, coalition-building, and sustained participation in policy processes is essential for enhancing its prophetic and participatory role in governance.